Psychotropic substances and public health problems : report of a seminar convened by the World Health Organization with the collaboration of the government of Finland and the United Nations Fund for Drug abuse control - Idänpään-Heikkila, Juhana; Khan, Inayat; United Nations Fund for Drug Abuse Control; WHO Seminar on Public Health Problems and Psychotropic Substances (1981 : Helsinki, Finland) (Helsinki : Government of Finland, 1982)
Hoe pak je de drugsproblematiek best aan?